Detection of early neoplastic changes in experimentally induced colorectal cancer using scanning electron microscopy and cell kinetic studies. Issue 7 (July 1984) - Cooke, T; Kirkham, N; Stainthorp, D H; Inman, C; Goeting, N; Taylor, I
Abstract : Colonic tumours were induced in Wistar rats using 12 consecutive subcutaneous injections of azoxymethane at a dose of 10 mg/kg/week. Pairs of rats were killed at five weekly intervals after initial injection until 25 weeks. Colonic mucosa was sampled from five standard areas along the length of the colon and examined by both scanning electron microscopy and conventional light microscopy. The crypt cell production rate was measured by stathmokinetic techniques. Scanning electron microscopy showed microadenomas as early as five weeks and consistently after 15 weeks. They were found predominantly in the distal colon and increased in size with time. The lesions showed a progressive increase in the number of crypts per adenoma and increasingly disorganised slit shaped crypt orifices. The presence of epithelial dysplasia in the microadenomas and of invasion of the colonic wall by carcinoma was confirmed histologically, although fewer lesions were identified in tissue sections than by scanning electron microscopy. Crypt cell production rate increased with time, particularly in the distal colon. This increase was significant between five and 25 weeks. The results of these observations suggest that there is an adenoma-carcinoma sequence in this animal model. The value of scanning electron microscopy in identifying and quantifying the mucosal changes during carcinogenesis is emphasised.